The Effect of Electric Field on Charcoal Conductivity in Supercapacitor Applications: Tectona Grandis Carbon and NaCl Electrolyte: Effect of Electric Field on Charcoal Conductivity in Supercapacitor Applications: Tectona Grandis Carbon and NaCl Electrolyte - Sukma, Melani Dyah Ayu; Abdul Hafar As Ari; Suparno; Wipsar Suhu Brams Dewandaru, Wipsar Suhu Brams Dewandaru; Bayu Setiaji, Bayu Setiaji (JST (Jurnal Sains dan Teknologi), 2025)
One of the biggest challenges in the application of renewable energy is efficient and sustainable energy storage. In this case, supercapacitors can be a solution as an efficient and sustainable energy storage. This study aims to determine how the relationship between activated carbon charcoal with NaCl as an electrolyte solution, as well as the potential generated by using variations in the concentration of electrolyte solution as much as 1 M, 2M, and 3 M. Characterisation tests conducted in this study include PSA (Particle Size Analyze) test to determine the particle size contained in wood charcoal activated carbon and XRD (X-Ray Difraction) to determine the composition of the material in wood charcoal activated carbon. The results showed that based on the PSA and XRD characteristics test, wood charcoal activated carbon has a particle arrangement measuring 327 nm which is suitable for supercapacitor applications and has an amorphous shape which is also a form of carbon suitable for supercapacitor applications, based on experimental results there is a relationship between wood charcoal activated carbon and NaCl as an electrolyte solution, and the potential associated with the output value of voltage, output value of electric current, and output value of capacitance produced by supercapacitors.